Pengaruh Oligarki Dalam Pilkada Ogan Ilir 2015 - Kurniawan, Mohd (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research is about the local oligarchy in the 2015 election of Ogan Ilir. The purpose of this study is to find out how the local political oligarchy occurred in the Ogan Ilir election. And what factors caused the local political oligarchy. This study uses Jeffrey A. Winter's theory, Oligarchy typology, political resources, and Vedi R. Hadiz's theory, Oligarchy operationalization patterns at the local level. This research method uses qualitative research with a political sociology approach. Then the data sources are parties who are able to read from the local level oligarchic movements from academics, socio-political observers, mass organizations engaged in socio-political and also data from related agencies such as election organizers, data collected through the observation process. , in-depth interviews and documentation, data analysis through data reduction, data presentation and conclusions. The results showed that the 2015 Ogan Ilir Pilkada became Oligarchy when the candidate pairs for the Ogan Ilir Pilkada appeared to have political advantages that were exclusively individual and also came from among the local political elite families. official position, formal political rights, intervention power, mobilization power, and material power.